A silica-based gel electrolyte system for improving the cycle performance of LiFePO4 batteries in an aqueous medium. Issue 3 (4th January 2016) - Pan, J. L.; Yin, Y.; Wen, Y. H.; Bai, S. L.; Cheng, J.; Cao, G. P.; Yang, Y. S.
Abstract : Cycling performance of LiFePO4 electrodes in aqueous and gel electrolytes at a 0.5C rate. Abstract : LiFePO4 based aqueous lithium batteries using aqueous electrolytes suffer from poor cycling performance. This is mainly caused by the Fe dissolution and Li loss generated from the effects of water. In this paper, fumed silica based gel electrolytes were prepared and optimized for improving the cycling performance of the LiFePO4 electrodes owing to superior stability and comparable ionic conductivity. It was manifested that the Zn/LiFePO4 cells using this homogenous gel electrolyte showed stable charge/discharge voltage profiles and excellent cycling performance at room temperature. The dissolution of Fe and the loss of Li in this electrolyte is significantly suppressed. These superior performances could endow this gel electrolyte as a promising alternative to aqueous electrolyte systems in the LiFePO4 batteries at room temperatures.